Combined Activity of the Redox-Modulating Compound Setanaxib (GKT137831) with Cytotoxic Agents in the Killing of Acute Myeloid Leukemia Cells - Muhammed Burak Demircan; Peter C. Mgbecheta; Anne Kresinsky; Tina M. Schnoeder; Katrin Schröder; Florian H. Heidel; Frank D. Böhmer (MDPI AG, 2022)
Acute myeloid leukemia (AML) cells harbor elevated levels of reactive oxygen species (ROS), which promote cell proliferation and cause oxidative stress. Therefore, the inhibition of ROS formation or elevation beyond a toxic level have been considered as therapeutic strategies. ROS elevation has recently been linked to enhanced NADPH oxidase 4 (NOX4) activity. Therefore, the compound Setanaxib (GKT137831), a clinically advanced ROS-modulating substance, which has initially been identified as a NOX1/4 inhibitor, was tested for its inhibitory activity on AML cells. Setanaxib showed antiproliferative activity as single compound, and strongly enhanced the cytotoxic action of anthracyclines such as daunorubicin in vitro. Setanaxib attenuated disease in a mouse model of FLT3-ITD driven myeloproliferation in vivo. Setanaxib did not significantly inhibit FLT3-ITD signaling, including FLT3 autophosphorylation, activation of STAT5, AKT, or extracellular signal regulated kinase 1 and 2 (ERK1/2). Surprisingly, the effects of Setanaxib on cell proliferation appeared to be independent of the presence of NOX4 and were not associated with ROS quenching. Instead, Setanaxib caused elevation of ROS levels in the AML cells and importantly, enhanced anthracycline-induced ROS formation, which may contribute to the combined effects. Further assessment of Setanaxib as potential enhancer of cytotoxic AML therapy appears warranted.